Oral Lichen Planus as a Late Manifestation of Chikungunya Fever in the Oral Mucosa - Roberta Rayra Martins‐Chaves; Marina Rocha Fonseca Souza; Laura Freitas Xavier; Larissa Rany Martins‐Chaves; Ana Carolina Carneiro Batista deOliveira; Ricardo Santiago Gomez (Clinical Case Reports)
ABSTRACT Chikungunya fever is a viral disease transmitted to humans by mosquitoes. Persistent polyarthritis or polyarthralgia morning stiffness and asthenia may last from serveral months to over three years after the disease onset. A 47‐year‐old non‐smoker was referred for evaluation of multiple bilateral interlacing white plaques and papules associated with erosive areas in the buccal mucosa and the tongue's border and ventral surface. The patient had contracted chikungunya fever ten months earlier and had since experienced ongoing arthralgia and diarrhoea. At the time of the consultation and no dermatological lesions were observed. The microscopic exam of the incisional biopsy was consistent with the diagnosis of interface mucositis. While late mucocutaneous manifestations of chikungunya fever are reported in the literature including the flare‐ups of preexisting dermatological lichen planus and psoriasis the patient was not taking any medication this is the first documented case of oral lichen planus onset associated with this condition.